Study on Photholes - Manoj Yadav, B; Anusha, N (International Journal of Engineering and Technology, 2018)
This paper highlights pothole detection methods and identifies a cost-effective solution for potholes in order to give timely alerts to drivers to avoid accidents and vehicle damages.Â Â